Que fatores determinam as escolhas alimentares de micos-de-cheiro? - OLIVEIRA, Bárbara Cunha de (Universidade Federal do Pará, 2018)
The nutritional composition of the diet influences the survival and reproductive success of an animal. In primates, food choices may be related to specific nutritional demands of male and female reproduction and may be affected by the social position of individuals. The objective of this study was to evaluate if gender, social status and reproductive cycle phases affect the food choices of adult squirrel monkeys (S. collinsi). Food and agonistic behaviors of 13 males and 19 females were observed in three phases of the reproductive cycle. It was evaluated if males and females differ in intake and consumption of macronutrients and if hierarchical position is related to macronutritional consumption. Anova's repeated measures were taken to evaluate if the diet has changed between the phases of the reproductive cycle. Sex differences in food choices were detected only in the reproductive phase when females consumed more protein, lipids and fiber than males, while males consumed more water than females. No social position effects were detected on nutrient intake. When comparing differences in nutritional intake between the phases of the reproductive cycle, it was detected that females significantly increased the carbohydrate intake and the intake rate during the Reproductive phase and lipids, fibers and water in the Pre-reproductive and Reproductive phases. Males increased the consumption of fibers in the Pre-reproductive and Reproductive phases and water increasing progressively until the Reproductive phase. The results reflect differences in the reproductive strategy of males and females: While females invest in food consuming nutrients related to the quality of gestation and lactation, males invest in maintaining the fat/swollen appearance, possibly related to females' attraction.